Analisis Pengaruh Praktek Work Life Balance, Kepuasan Kerja, dan Tingkat Stres terhadap Retensi Karyawan di Industri Perbankan di Indonesia - Susilawati, Made (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research aims to analyze the influence of Work Life Balance (WLB) practices, job satisfaction, and stress levels on employee retention in the banking industry in Indonesia. The survey method was used to collect data from 350 respondents. The results of the analysis show that WLB practices and job satisfaction have a significant positive influence on employee retention, while stress levels have a significant negative influence. Mediation analysis shows that job satisfaction mediates the relationship between WLB practices and employee retention, as well as between stress levels and employee retention. In conclusion, banking company management needs to pay attention to and improve WLB practices, manage work stress, and pay attention to factors that influence job satisfaction to retain quality and committed employees in the long term. Keywords: Banking Industry, Employee Retention, Indonesia, Job Satisfaction, Stress Levels, Work Life Balance Practices.